2015
DOI: 10.1007/s10103-015-1748-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of different energy delivery settings in laser and LED phototherapies in the inflammatory process of rat’s TMJ induced by carrageenan

Abstract: Temporomandibular disorders (TMDs) are mostly inflammatory conditions widespread in the population. Previous studies have shown positive effects of either laser or light-emitting diode (LED) phototherapies on treating TMDs, but their action and mechanism in the inflammatory infiltrate of the temporomandibular joint are still poorly understood. The aim of this study was to assess, through histological analysis, the effectiveness of using laser light (λ 780 nm, 70 mW, continous wave (CW), 10 J) and LED (λ 850 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The criteria of histological evaluation were the percentage of neutrophils and lymphocytes in relation to the total of cells in the observed area, and the percentage of blood vessels in relation to the observed area. [34] Prior to this, a study investigated the effects of phototherapy with the combination of different light sources on the nonspecific pain of a larger joint: the knee. The combination of 905 nm super-pulse laser and 875 and 640 nm LEDs were used, which proved effective in reducing pain and improving quality of life in patients with knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria of histological evaluation were the percentage of neutrophils and lymphocytes in relation to the total of cells in the observed area, and the percentage of blood vessels in relation to the observed area. [34] Prior to this, a study investigated the effects of phototherapy with the combination of different light sources on the nonspecific pain of a larger joint: the knee. The combination of 905 nm super-pulse laser and 875 and 640 nm LEDs were used, which proved effective in reducing pain and improving quality of life in patients with knee pain.…”
Section: Discussionmentioning
confidence: 99%
“…The highest peak is in the near infrared window at 812.0-846 nm. Additionally, PBMT in the near infrared window has shown efficacy for several other inflammatory/painful indications, such as osteoarthritis, colitis, and temporomandibular disorders [29][30][31][32][33][34][35][36]. Longer wavelengths beyond the near-infrared range lack evidence of efficacy [37].…”
Section: Wavelengthmentioning
confidence: 99%
“…Panhoca et al [42] showed that low-level R-NIR photo-stimulation can be useful in improving outcomes related to pain relief and mandibular range of motion for TMD patients, while de Castro et al [43] reported reduction of inflammatory infiltrate in the TMJ. These effects could explain similar results reported by Do gan et al [25] for extra-oral application of plasma electrodes in direct contact with the skin in projection of the underlying TMJ.…”
Section: Emission Spectrum Analysismentioning
confidence: 99%